Randomized Controlled Pilot Trial of Behavioral Insomnia Treatment for Chronic Migraine With Comorbid Insomnia. Issue 2 (27th January 2016) - Smitherman, Todd A.; Walters, A. Brooke; Davis, Rachel E.; Ambrose, Carrie E.; Roland, Malcolm; Houle, Timothy T.; Rains, Jeanetta C.
Abstract : Background: Migraine frequently co‐occurs with and is triggered by sleep disturbance, particularly insomnia, and the large majority of patients with chronic migraine (CM) have comorbid insomnia. Limited evidence suggests that behavioral regulation of sleep may reduce migraine frequency, but studies to date have not assessed the viability of stimulus control and sleep restriction interventions or included objective measurement of sleep parameters. The aim of this study, thus, was to pilot‐test the efficacy of a brief behavioral insomnia intervention for adults with CM and comorbid insomnia; headache diaries and actigraphy were included to assess outcomes throughout the trial. Methods: This randomized parallel‐arm pilot trial recruited adults with both CM and comorbid insomnia. Participants were randomly assigned to three 30‐minute biweekly sessions of cognitive‐behavioral therapy for insomnia (CBTi) or control treatment. Participants were blinded to treatment and control conditions to control for outcome expectations. Each treatment condition involved training in and daily practice in 5 instructions/skills. The CBTi group learned and practiced skills pertaining to stimulus control and sleep restriction. The control intervention was the same as used by Calhoun and Ford (2007) and involved training in and daily practice of skills pertaining to keeping a consistent food/liquid intake, range of motion exercises, and acupressure. Participants provided outcome data via daily headache diaries, actigraphy, and self‐report measures. The primary outcome was reduction in headache frequency at 2 weeks post‐treatment and 6‐week follow‐up; secondary outcomes included other headache parameters, objective actigraphic and subjective changes in sleep, and treatment effect sizes and perceived credibility. Generalized estimating equations with a binomial logit link and inverse probability weights were used to assess the primary outcome among the intent‐to‐treat sample, and repeated measures generalized linear models were used to assess changes in secondary outcomes after controlling for baseline values. Results: The intent‐to‐treat analyses included 31 adults (M age = 30.8 [12.9] years; 90.3% female; 80.6% white) with CM and comorbid insomnia. Both interventions yielded reductions in headache frequency at post‐treatment (26.9% reduction for CBTi vs 36.2% for control) and follow‐up (48.9% for CBTi vs 25.0% for control). At follow‐up the odds of experiencing headache were 60% lower for CBTi than for control treatment, indicative of a large effect size that did not reach statistical significance after Bonferroni correction for assessing two primary endpoints (odds ratio: 0.40; 95% CI: 0.17, 0.91; P  = .028). CBTi produced significantly larger increases than control treatment in total sleep time and sleep efficiency as quantified by actigraphy, as well as in self‐reported insomnia severity. Adherence was high and treatments were perceived as credible without differences between groups, but the control group experienced a higher rate of dropouts. No adverse events were reported. Conclusions: Behavioral treatment of comorbid insomnia in individuals with CM produced large reductions in headache frequency, though some improvement in headache occurred with a behavioral intervention not focused on modifying sleep. Among the CBTi group only, both headache frequency and sleep parameters continued to improve after treatment, suggesting the presence of enduring effects over time. Directly treating insomnia using components of stimulus control and sleep restriction holds promise for reducing comorbid migraine. Development of and comparison to a truly inert pseudotherapy control presents unique challenges that future studies should address.